2006
DOI: 10.1186/cc4913
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, randomized trial comparing fluids and dobutamine optimization of oxygen delivery in high-risk surgical patients [ISRCTN42445141]

Abstract: Introduction Preventing perioperative tissue oxygen debt contributes to a better postoperative recovery. Whether the beneficial effects of fluids and inotropes during optimization of the oxygen delivery index (DO 2 I) in high-risk patients submitted to major surgeries are due to fluids, to inotropes, or to the combination of the two is not known. We aimed to investigate the effect of DO 2 I optimization with fluids or with fluids and dobutamine on the 60-day hospital mortality and incidence of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…A baseline mortality rate of >20% is unusual in current practice [4,96]; in this sense it is interesting to note that two of five studies with a baseline mortality rate of >20% were carried out within the past decade. Neither of these studies demonstrated a survival benefit with GDT [80,97]. One of these studies demonstrated a reduction in complication rates [97], whilst the other demonstrated a trend towards a reduction in complication rates [80].…”
Section: Discussionmentioning
confidence: 99%
“…A baseline mortality rate of >20% is unusual in current practice [4,96]; in this sense it is interesting to note that two of five studies with a baseline mortality rate of >20% were carried out within the past decade. Neither of these studies demonstrated a survival benefit with GDT [80,97]. One of these studies demonstrated a reduction in complication rates [97], whilst the other demonstrated a trend towards a reduction in complication rates [80].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in patients with a high risk of perioperative death, PAC-guided hemodynamic optimization using dobutamine to obtain DO 2 >600 ml/minute/m 2 was associated with better outcomes, whereas fluids alone increased the incidence of postoperative complications [45]. The use of two different treatment algorithms of GDT comparing fluids alone with fluids and dobutamine suggests that dobutamine was associated with better recovery of the left ventricular stroke work index during operative trauma and with higher tolerance to fluids.…”
Section: What Are the Best Hemodynamic Targets?mentioning
confidence: 99%
“…In spite of the multifactorial origin of postoperative complications, compromised physiologic reserves and multiple comorbidities in combination with extensive surgery seem to be a hallmark of high complication and mortality rates [44]. In general, these patients are older, undergoing extensive ablative surgery with limited cardiopulmonary reserve, and/or with other organ dysfunctions/comorbidities (Figure 2) [38,45,65]. Shoemaker and colleagues' criteria for identifying a high-risk of perioperative complications will also identify patients to be managed in this group [35].…”
Section: Which Targets For Which Patients?mentioning
confidence: 99%
“…O desbalanço entre oferta e consumo de oxigênio tecidual ocorre particularmente no intraoperatório e nas primeiras horas após o término da cirurgia. A redução da oferta de oxigênio nesse contexto está associada à redução da oxigenação global, hipoperfusão tecidual e a maior ocorrência de complicações pós-operatórias [274][275][276][277][278][279][280] .…”
Section: ) Monitorização Hemodinâmicaunclassified